P4_5 Atmospheric ODSTs - Jupp, M.; Cobley, D.; Yeomans, K.; Fenlon-Smith, D. (Physics Special Topics, 2016)
In this paper the maximum acceleration on the ODST and the pod was found to be -4g, with a braking thrusters force of 14100 N during the last 50 m of descent. This deceleration brings the impact velocity of the pod to below velocity of 1 ms^-1, should the braking thrusters fail to fire the pod will hit the ground with a velocity of 43.2 ms^-1 killing the trooper.